Effects of phosphorus on uptake and translocation of methylmercury in rice. Issue 1 (2nd January 2018) - Gao, Axiang; Zhou, Xinbin; Zhang, Chengming; He, Xinhua
ABSTRACT: The aim of this study was to determine uptake and translocation of MeHg in the absence or presence of P in three rice cultivars, named Tianyou196 (TY196), NanJing35 (NJ35), and ZiXiangnuo (ZX). Rice seedlings from each cultivar were divided into two groups. One group was grown in normal P (+P) nutrient solution and the other in absence of P or starvation (−P) nutrient solution for 2 weeks. Both groups were subsequently exposed to 200 mg/L MeHg chloride culture solution and maintained in a greenhouse for 4 weeks. The results showed that the amount of reddish Fe plaque outside rice root was significantly increased by P starvation treatment, but in the +P treatments, rice roots remained white. It is proposed that Fe plaque formed sequestered MeHg and consequently reduced translocation of MeHg from roots to shoots. It is of interest that MeHg content in roots and shoots of TY196 and NJ35 was 11.1%–18.8% and 28.9%–32.3% lower than in ZX, respectively. Therefore, in practice, depletion of P to enhance Fe plaque formation in rice growing area is effective in preventing MeHg translocation from roots to shoots and ensures food safety in mine locations.